Method, Substance, and the Future of African Philosophy (Springer International Publishing, 2018)
This book takes stock of the strides made to date in African philosophy. Authors focus on four important aspects of African philosophy: the history, methodological debates, substantive issues in the field, and direction for the future. By collating this anthology, Edwin E. Etieyibo excavates both current and primordial knowledge in African philosophy, enhancing the development of this growing field.